Nuevo León durante la independencia de Texas, 1835-1836 - González Quiroga, Miguel Ángel (El Colegio de México, A.C., 2006)
The new-born Mexican Republic suffered one of its strongest shocks in 1836, during the Texas War. The impact of this conflict in the neighbouring state of Nuevo Leon is the main subject of this work, which also describes the situation of Mexico and its army, as well as the state's reaction towards the centralist shift — Texas' main argument  for splitting from Mexico. The study of the separation of Texas, widely reviewed in Mexican historiography, is enriched through the viewpoint of one of the most affected states.